2022
DOI: 10.3390/bs12010010
|View full text |Cite
|
Sign up to set email alerts
|

Personality, Defense Mechanisms and Psychological Distress in Women with Fibromyalgia

Abstract: Background: Previous studies have shown that many personality traits are associated with fibromyalgia (FM), worsening both the quality of life and psychological distress of patients. Despite the high comorbidity of psychopathological disorders in this syndrome and their association with immature defense styles, few studies have examined the defense mechanisms used by FM patients. The main aim of our study was to investigate personality traits and defense mechanisms in FM patients compared to in a healthy contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 53 publications
1
17
0
Order By: Relevance
“…These explanations of defense mechanisms as automatic processes that reduce and mitigate the harmful effects of pain by regulating the emotional response of individuals were given by Valliant in describing adaptive mental mechanisms [ 63 ]. Similar results were confirmed in patients with fibromyalgia, who developed significantly stronger defense mechanisms compared to healthy individuals [ 64 ]. However, an interesting result is that the area of physical limitation and functioning was significantly negatively associated with the estimated pain intensity.…”
Section: Discussionsupporting
confidence: 75%
“…These explanations of defense mechanisms as automatic processes that reduce and mitigate the harmful effects of pain by regulating the emotional response of individuals were given by Valliant in describing adaptive mental mechanisms [ 63 ]. Similar results were confirmed in patients with fibromyalgia, who developed significantly stronger defense mechanisms compared to healthy individuals [ 64 ]. However, an interesting result is that the area of physical limitation and functioning was significantly negatively associated with the estimated pain intensity.…”
Section: Discussionsupporting
confidence: 75%
“…Past studies have demonstrated a strong correlation between trauma, dissociation, and FM symptomatology [8,9]. In addition, early traumatic experiences seems to be a risk factors for developing widespread pain in adulthood including FM symptoms by excessively activating stress responses during a critical period of development through hyperalgesic priming [10].Hence, FM patients may be particularly vulnerable to pandemicrelated increase of depression and anxiety and possibly worsening of their clinical pain [11][12][13]. However, as the COVID-19 pandemic upended everyday life, many online surveys demonstrated that negative affect also increased among the general population [14,15].…”
Section: Introductionmentioning
confidence: 98%
“…These studies address theoretical and practical advances on personality in different populations and age groups, as well as the research findings of interventions and treatment strategies involving personality. Of the seven original research articles and one scoping review on personality included in this Special Issue, three are focused on healthy adult populations [ 1 , 2 , 3 ], two in healthy children and adolescent [ 4 , 5 ], other two in chronic pain conditions (migraine [ 6 ] and fibromyalgia [ 7 ]) and one in personality disorders (cluster B and C [ 8 ]). The variety of conditions, populations, personality traits and research methods used in the included studies makes difficult a direct comparison of the findings but provide a wider approach to personality, intervention, and psychological treatment.…”
mentioning
confidence: 99%
“…The study of Romeo et al [ 7 ] is characterized by its novelty in exploring the contribution of both defense mechanisms and personality characteristics on the psychological distress of fibromyalgia patients. Associations between personality traits (alexithymia, harm avoidance, cooperativeness, persistence), defense mechanisms (adaptive and maladaptive defense style, image-distorting, and self-sacrificing) and psychological distress (anxiety and depression) in fibromyalgia patients and healthy controls were explored.…”
mentioning
confidence: 99%
See 1 more Smart Citation